FACTORS OF DEVELOPING OF INTERCULTURAL COMMUNICATION COMPETENCE IN TEACHING ENGLISH TO CADETS OF MILITARY UNIVERSITY - Musayeva Shaxzoda Ibroximovna (Лучшие интеллектуальные исследования, 2024)
This article discusses the role of English language teaching in cadets' intercultural communication competence. The article explores how to develop intercultural communication competencies of English learners in English teaching, as well as understanding the important goals of English teaching.